2020
DOI: 10.1002/ajmg.a.61561
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome of prenatally diagnosed boys with 47,XXY (Klinefelter syndrome) and the potential influence of early hormonal therapy

Abstract: This cross‐sectional study examined the neurodevelopment of a large, prenatally diagnosed population of boys with 47,XXY; investigated the potentially positive effects of early hormonal therapy (EHT) on language, cognition, and motor in this population; and identified novel at risk biomarkers associated with 47,XXY. Two‐hundred and seventy two evaluations were collected from 148 prenatally diagnosed boys with 47,XXY between 0 and 36 months and separated into one of three groups, depending on visit age: Y1 (0–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Four cases showed Three patients had NIPT results that showed copy number variants of X chromosome (Table 9). Amniocentesis confirmed de novo 46,X,idic(X)(p11.21) in patient 51, maternally inherited 46,X,del(X)(p21) in patient 52, and 45,X,inv(19)(p11q13.1)[15]/46,X,r(X)(p22.1q21),inv (19) [10]/46,X,inv (19),+mar [5] in patient 53. They opted for continuation of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four cases showed Three patients had NIPT results that showed copy number variants of X chromosome (Table 9). Amniocentesis confirmed de novo 46,X,idic(X)(p11.21) in patient 51, maternally inherited 46,X,del(X)(p21) in patient 52, and 45,X,inv(19)(p11q13.1)[15]/46,X,r(X)(p22.1q21),inv (19) [10]/46,X,inv (19),+mar [5] in patient 53. They opted for continuation of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Although the miscarriage risk of prenatal invasive diagnostic procedure is low (0.20% for chorionic villus sampling and 0.30% for amniocentesis) 16 , if the definitive diagnosis is unlikely to affect continuation of pregnancy, diagnostic testing may be deferred until after delivery. Knowing the genetic diagnosis can help timely interventions (such as hormone replacement therapy and educational support) and optimise clinical outcomes [17][18][19] . Patient autonomy should be respected, and their decisions should be supported.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between exogenous testosterone administration in infancy and developmental benefits during childhood have been reported 42 . It is suggested that consideration of this treatment should be given to all infants with KS, based on an assumed testosterone deficiency.…”
Section: Postnatal Issues In Confirmed Ksmentioning
confidence: 99%
“…Discussion is not recommended in routine clinical care around associations between exogenous testosterone administration in infancy and developmental benefits during childhood 42 as this treatment remains controversial 43 . At present, early review and assessment by a paediatric endocrinologist with individualised intervention on the basis of clinical need is recommended.…”
Section: What Options For Postnatal Therapy Are Available In Ks?mentioning
confidence: 99%
“…Although not standard of care, hormonal treatment using testosterone has been associated with significant improvements in neurodevelopmental and behavioral outcomes in males with 47,XXY as well as 49,XXXXY for over 25 years (Galasso, Arpino, Fabbri, & Curatolo, 2003;Linden et al, 1995;Mazzilli et al, 2016;Patwardhan, Eliez, Bender, Linden, & Reiss, 2000). Studies in recent years have begun to investigate the possible benefits of testosterone treatment at younger ages in these disorders as well, including early hormonal treatment in infancy (Samango-Sprouse et al, 2013, 2015, 2020 and hormonal booster therapy in later childhood (Samango-Sprouse et al, 2018;Samango-Sprouse, Lasutschinkow, Powell, Sadeghin, & Gropman, 2019;Tran, Samango-Sprouse, Sadeghin, Powell, & Gropman, 2019). While many studies on the impact of testosterone have been completed on 47,XXY, studies on 49,XXXXY have been mostly limited to case studies, incidental reports, and small sample sizes.…”
Section: Introductionmentioning
confidence: 99%